ANALISA DAN KLASIFIKASI SENTIMENT OPINI PENONTON PADA WEBSITE IMDB.COM DENGAN ALGORITMA SUPPORT VECTOR MACHINE - Cindy Claudia Budi Wasito, Elis Sondang Dasawaty (Jurnal Informatika dan Bisnis, 2016)
In its development, information technology brought about many changes and advances in the context of everyday life. One of the benefits of information technology to process and process large amounts of data is data mining and text mining. In this study the authors will analyze and discuss the sentiment (emotion) contained in a comment or post on reviews given by the audience on a movie and see whether it will be classified as positive sentiment or negative so that it can be used to classify the reviews on different movies at imdb.com in the future.Â Key words: Classification, Sentiment Analysis, Support Vector Machine